IDENTIFIKASI PAUD HI (HOLISTIK INTEGRATIF) DI KOTA MATARAM TAHUN 2024 - Juliana, Wika; Suarta, I Nyoman; Rachmayani, Ika; Nurhasanah, Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
PAUD HI (Holistic Integrative) is comprehensive treatment of early childhood which includes five services. The aim of this research is to identify Holistic Integrative (HI) programs in Kindergartens (TK), RA and KB in Mataram City in the years 2023-2024. This research method is descriptive quantitative research with survey research methods. The sampling technique used in this research is the Proportional Stratified Random Sampling technique, with a population of 292 heads of institutions and a sample of 20% or 24 institutions. The data collection tool used was a questionnaire. The research result show that as many as 75% of learning services are holistically integrative, 100% of institutions have collaborated with other nutrition and health sectors or agencies with 54, 17 establishing formal relationship and strengthening this with a letter of cooperation between both parties, 43, 83% institutions have involved parents in supporting activities at PAUD institutions in the form of POM (Parents Associotion Organization or Parent Student Association) and 25% of institutions already have clear letters of cooperation or decrees, 45, 83% of institutions have collaborated with agencies and organizations other field groups formally and 87, 5% of institutions have provided welfare in instutional units that is holistically integrative. Based on the research result above, it can be concluded that the identification of holistic integrative (HI) PAUD in Mataram City in 2023-2024 has been implemented optimally.